The Buddy files : the case of the missing family - Butler, Dori Hillestad (Butler, Dori Hillestad. Buddy files, 2010)
Buddy the dog risks everything when he leaves his new family to investigate what happened to Kayla and her father, his beloved former owners, by slipping into a van Kayla's uncle is using to empty her house in the middle of the night.